Association Between Religiosity and Happiness Among a Group of Muslim Undergraduate Students - Sahraian, Ali (Journal of religion and health, 2013)
The association between religiosity and happiness has been the focus of much recent research. The majority of them report a positive correlation between a religious attitude and behavior and the level of happiness. However, different findings have been reported. The aim of the current study was to test link between religiosity and happiness among a group of undergraduate Muslim students. Two hundred and seventy-one health-related students agreed to participate and completed Oxford Happiness Index and a religious belief questionnaire. It was found that higher score on religious belief was significantly linked to the level of happiness (r = .256, P = .01). The result confirms that individuals with a more religious attitude experience more happiness. The result of this study should be considered in programs designed to improve overall well-being of university students.